The Exegesis of Shaykh Abdul Lathif Syakur: A Study of Manuscript Tafsir 28 and Its Nusantara Context - Aldomi Putra; M. Hariyadi; Abdur Rokhim Hasan; Muhammad Idris (ZAD Al-Mufassirin, 2026)
This study aims to produce a critical edition of of Tafsir 28, a Qur’anic commentary manuscript written by Shaykh Abdul Lathif Syakur (1882–1963), to reveal its epistemology and intellectual framework, and to examine its contents in order to identify the ways in which it reflects Nusantara Islamic thought and local cultural elements  in Shaykh Abdul Lathif Syakur’s interpretation. Tafsir 28 covers the Qur’anic chapters from Surah al-Mujādilah to Surah at-Taḥrīm. Shaykh Abdul Lathif Syakur’s interpretation is closely connected to the socio-cultural context of the Nusantara Muslim community. This research is qualitative in nature, combining library research and field research, and employing philological and textual taḥqīq approaches. This research finds that, this tafsir belongs to tafsīr bi al-ma’thūr, employs the ijmālī method. Tafsir 28 constitutes Shaykh Abdul Lathif Syakur’s contribution to the Nusantara Qur’anic exegesis. This work was accepted by the local community, despite remaining unpublished , because the interpretations contained in it were part of the teachings that Shaykh Abdul Lathif Syakur had delivered in his preaching, based on the analysis of the Tafsir 28 text. Elements of Nusantara Islam expressed through a distinct Minangkabau cultural framework are evident throughout the commentary. This tafsir represents his contribution to the global Muslim community.